Perilipin1 mediates milk fat synthesis in bovine mammary epithelial cells through SREBP1 phosphorylation - Benshun Yang; Meng Wang; Zhangqing Wu; Jianbing Tan; Yanhong Meng; Taoping Zhang; Linsen Zan; Wucai Yang (Animal Biotechnology)
This study investigates the role of Perilipin1 (PLIN1) in milk fat synthesis in bovine mammary epithelial cells (BMECs) and its regulatory mechanisms, aiming to provide a foundation for improving milk fat content through molecular breeding. BMECs were used as a model to analyze the effects of PLIN1 overexpression (OE-PLIN1) and interference (si-PLIN1) on milk fat synthesis and lipid-related gene expression using RT-qPCR, Western blot, and Oil Red O staining. Results show that OE-PLIN1 significantly enhances triglyceride (TAG) accumulation in BMECs (P < 0.01), upregulates lipid synthesis-related genes (such as PPARγ, C/EBPα, C/EBPβ, FABP4, FASN) (P < 0.05), and downregulates the mRNA expression of lipid breakdown-related genes (HSL, ATGL) (P < 0.05). Conversely, si-PLIN1 significantly reduces TAG accumulation (P < 0.05) and lowers the expression of lipid synthesis and breakdown genes (P < 0.05). Additionally, OE-PLIN1 combined with SREBP1 siRNA interference (si-SREBP1) did not have a significant impact on the mRNA and protein levels of SREBP1, but it significantly altered SREBP1’s phosphorylation, indicating that SREBP1 interference inhibits PLIN1’s effect on milk fat synthesis. This study suggests that PLIN1 promotes milk fat synthesis in BMECs via regulating SREBP1 activity, offering a new strategy for enhancing milk fat content in dairy cattle.